Summary of the 2021 ICRP workshop on the future of radiological protection. (1st June 2022) - Rühm, W; Clement, C; Cool, D; Laurier, D; Bochud, F; Applegate, K; Schneider, T; Bouffler, S; Cho, K; Hirth, G; Kai, M; Liu, S; et al.
Abstract: The International Commission on Radiological Protection (ICRP) has embarked on a process to review and revise the current System of Radiological Protection ('the System'). To stimulate discussion, the ICRP published two open-access articles: one on aspects of the System that might require review, and another on research that might improve the scientific foundation of the System. Building on these articles, the ICRP organized a Workshop on the Future of Radiological Protection as an opportunity to engage in the review and revision of the System. This digital workshop took place from 14 October–3 November 2021 and included 20 live-streamed and 43 on-demand presentations. Approximately 1500 individuals from 100 countries participated. Based on the subjects covered by the presentations, this summary is organized into four broad areas: the scientific basis, concepts and application of the System; and the role of the ICRP. Some of the key topics that emerged included the following: classification of radiation-induced effects; adverse outcome pathway methodologies; better understanding of the dose–response relationship; holistic and reasonable approaches to optimization of protection; radiological protection of the environment; ethical basis of the System; clarity, consistency and communication of the System; application of the System in medicine and application of the principles of justification and optimization of protection.